Governing Finance: Global Imperatives and the Challenge of Reconciling Community Representation with Expertise. - Clark, G (Clark University, 2008)
Although the regulation of financial institutions and global markets has been subject to extensive research and policy practice, regulation often comes second to governance: regulation cleans up failures of governance in the management and performance of private financial institutions and markets. There are two theories of the nature and practice of governance; one emphasizes its functional performance, whereas the other emphasizes its political foundations. In this article, I suggest that best practice seeks to reconcile functionalism with community representation and that representation is a virtue in its own right and need not be seen as antithetical to functional efficiency. To sustain these arguments, I note the distinctive characteristics of financial decision making under risk and uncertainty, using simple examples to underscore the benefits of good governance. I then present criteria for well-governed financial institutions, specifically public and private pension funds, with implications for best practice as illustrated by four case studies of funds from Canada, Europe, and the United States. The final section considers the lessons of these case studies for the design of sovereign wealth funds and raises questions as to whether there are limits to reconciliation, given the acceleration of global financial integration.